Iowa Birdline update, September 17, 1990 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Iowa Birdline update for September 17, 1990. Highlights of the update include sightings of a California Gull, a Red Knot, and a Black Rail. Other observations of note were of a Laughing Gull, Barn Owls, and numerous species of Warblers and shorebirds. Epson - sheet feed/flatbed